Conceptualizing the Role of Individual Agency in Mobility Transitions: Avenues for the Integration of Sociological and Psychological Perspectives - Ruhrort, Lisa; Allert, Viktoria (Frontiers in Psychology, 2021)
With the release of the latest IPCC report, the urgency to steer the transport sector towards ecological sustainability has been recognized more and more broadly. To better understand the prerequisites for a shift to more sustainable mobilitytransition to sustainable mobility patterns, we argue that interdisciplinary mobility research needs to revisit the interaction between social structures and individual agency by focusing on social norms. While critical sociological approaches stress the structural barriers to sustainable mobility, political discourse over sustainable mobility is still largely dominated by overly individualistic approaches, which focus on individual behaviour change neglecting its social embeddedness. With discursive struggles over sustainable mobility intensifying, it becomes more urgent to better understand how structural contexts condition individual mobility travel behaviour, while at the same time showing how individuals engage in processes of social change. Against this backdrop, the article seeks to deepen the cooperation between sociological and psychological research in mobility transitions research. Building on a broad body of literature, we revisit recent theoretical approaches, which conceptualize the role of individual agency in sustainability transitions. On this basis, we highlight the role of social norms in mobility transitions as a key concept bridging individual behaviour and social structures. Using Strong Structuration Theory as an integrative framework, we focus on the role of individual agency in processes of re-negotiation of social norms. Our main hypothesis is that individuals can contribute to mobility transitions by influencing and re-negotiating social norms, especially in the context of windows of opportunity. We analyze how focusing on the dynamic and conflicted nature of social norms can help to illustrate leverage points for a mobility transition as well as inspire future empirical research in the field. This includes that individuals can influence social norms through changing their own travel behavior as well as through engaging in discourse on transport policies.